Presentation: Popular devotion in the Andes: facticity and hermeneutics - Allpanchis, Revista (2007)
Andean time and space are evidently marked by popular Christian devotion. The ritual calendar of the man of the Andes is made up of Christian festivals that give religious meaning to their daily actions linked to agricultural or livestock life. The churches, built in the most remote places, continue to be a separate space dedicated to sacred worship, and the population continues to recognize the most relevant moments of Christian life as highly significant: baptism, first communion, marriage. Undoubtedly, one of the particularities of the Andean man is his sensitivity towards religion: he is frequently longing for hope, expectant of blessing, eager for reconciliation or desirous of the spirit of thanksgiving with processions, pilgrimages or traditional Catholic rituals. Time and space to ask, give thanks, repent, atone for sins, reconcile with the Creator.